Period Poverty in a Pandemic: Harnessing Law to Achieve Menstrual Equity - Bridget J. Crawford; Emily Gold Waldman (Washington University Law Review, 2021)
Period poverty is not new, but it has become more visible during the COVID-19 crisis. Worldwide, menstruation has long caused marginalization and vulnerability for many. The pandemic has only amplified these conditions. This Article makes three claims. The first is descriptive, identifying four interrelated aspects of global period poverty that have gained new salience during the coronavirus pandemic: lack of access to affordable menstrual products; lack of access to other needed supplies and services for health and sanitation; lack of menstruation-related information and support from schools and health professionals; and menstrual stigma and shame. Using examples from multiple countries, the Article highlights the importance of being able to manage one’s menstruation in a safe and affordable way. The Article’s second claim is that law has a role to play in eliminating period poverty—both during a pandemic and beyond. By ensuring that menstruation-related concerns are taken into account when defining “essential businesses,” for example, governments can both address the material needs of approximately half the population and signal that those needs are important. Finally, the Article explores the heightened visibility of menstruation-related concerns during the COVID-19 crisis as suggestive of an emerging popular awareness of period poverty. This Article’s account has important implications for a larger worldwide menstrual equity movement that takes aim at menstruation-related obstacles standing in the way of full participation for all people in private and public life.
Keywords: Menstrual equity; Period poverty; Menstrual products; Menstrual stigma; Tampon tax; Menstrual Equity for All Act